2012
DOI: 10.3758/s13428-012-0247-4
|View full text |Cite
|
Sign up to set email alerts
|

The influence of calibration method and eye physiology on eyetracking data quality

Abstract: Recording eye movement data with high quality is often a prerequisite for producing valid and replicable results and for drawing well-founded conclusions about the oculomotor system. Today, many aspects of data quality are often informally discussed among researchers but are very seldom measured, quantified, and reported. Here we systematically investigated how the calibration method, aspects of participants' eye physiologies, the influences of recording time and gaze direction, and the experience of operators… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
214
0
8

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 240 publications
(241 citation statements)
references
References 31 publications
11
214
0
8
Order By: Relevance
“…For instance, Nyström, Andersson, Holmqvist, and van de Weijer (2013) showed that when recorded using a SensoMotoric Instruments (SMI) HiSpeed 1250 tower eye-tracker, blue eyes result in data with a poorer RMS(S2S) precision than brown eyes, and that data recorded from participants with glasses are more imprecise than data from uncorrected eyes in this particular eye-tracker. Increasing the pixel resolution at the eye (e.g., by using a higherresolution camera or placing it closer to the eye) makes precision better [lower RMS(S2S) or SD].…”
mentioning
confidence: 99%
“…For instance, Nyström, Andersson, Holmqvist, and van de Weijer (2013) showed that when recorded using a SensoMotoric Instruments (SMI) HiSpeed 1250 tower eye-tracker, blue eyes result in data with a poorer RMS(S2S) precision than brown eyes, and that data recorded from participants with glasses are more imprecise than data from uncorrected eyes in this particular eye-tracker. Increasing the pixel resolution at the eye (e.g., by using a higherresolution camera or placing it closer to the eye) makes precision better [lower RMS(S2S) or SD].…”
mentioning
confidence: 99%
“…Las métricas que usualmente se utilizan para evaluar estos dispositivos son la precisión y la exactitud, expresadas en grados angulares. Estas medidas se llevan a cabo bajo condiciones controladas de luz y restringiendo los movimientos de la cabeza (Nyström, Andersson, Holmqvist, & van de Weijer, 2013). La evaluación con estas dos métricas está centrada en medir la calidad del dispositivo, que sirve de interfaz de acceso al ordenador.…”
Section: Evaluación De La Interacción: Un Problema No Resueltounclassified
“…Calibration was executed before starting the experiment, as this has great importance for examining vergence (see, e.g., Nyström et al, 2013). Using video-based eye tracking, estimates of the gaze position always relate to the calibrated positions.…”
Section: Methodsmentioning
confidence: 99%
“…359-365. DOI: 10.1515/prolas-2017 eyelashes...) were already mentioned as possible sources of variation in other studies (Nyström et al 2013). Kirkby et al (2013) investigated the hypothesis that one potential source for the contradictory findings may be related to different devices used to collect the data as well as the different methods used for analysis.…”
Section: Introductionmentioning
confidence: 99%